THE MILLENNIAL GENERATION AND POPULAR CULTURE IN EFL CLASSROOM - Farhanaz Rabbani (Universitas Kuningan, 2015)
Writing instructors all over the world are facing new challenges in teaching writing to students who belong to the rapidly evolving digital age. These multitasking youngsters are popularly referred to as Generation Y or the Millennial Generation and are the most connected generation of the century. With the dissemination of digital communication, popular culture and online networking have become an integral part of Generation Y. Teachers need to address this connectedness and focus on a curriculum based on Communicative Language Teaching (CLT) where interactive activities are highlighted. The financially and technologically savvy Generation Y-ers want to use a discourse they are familiar with and work with materials on popular culture. This paper shows the necessity of popular culture in teaching literature and academic writing courses to the Generation Y students because popular culture is the new global culture. Teachers need to use classroom materials and resources for formal, informal discourse and computer mediated discourse (CMD).